Corpo, educação física e material didático: a construção de interfaces - Fernando Garcez (Universidade Estadual do Oeste do Paraná, 2015)
That essay explores the idea of the knowledge about the body disseminated by education as a strategy they use educational materials to achieve outcome. Recovers on authors such as Le Breton and Ghiraldelli Jr. body vicissitudes, central theme for Physical Education. The materials didactic are immersed a single match of forces and should not be discarded beforehand, but placed under scrutiny. By this way, the construction of interfaces can be fruitful.